Parasitic Protozoa found in the skin, gills, and intestines of Patin Catfish (Pangasius hypophthalmus) and Common Carp (Cyprinus carpio) - Veenu Kumar; Arifin Budiman Nugraha; Umi Cahyaningsih; Tara Puri Ducha Rahmani (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
The parasitic protozoa found in